A catechin-modified carbon paste electrode for electrocatalytic determination of neurotransmitters. Issue 13 (17th June 2015) - Wei, Juan; He, Jianbo; Chen, Changlun; Wang, Xiangke
Abstract : Catechin was electropolymerized on an activated carbon paste electrode for electrocatalytic determination of dopamine and serotonin. Abstract : Catechin is a polyphenol antioxidant which can be found in great abundance in the leaves of tea plants. In this study, catechin was electrodeposited on an activated carbon paste electrode for electrocatalytic determination of two neurotransmitters, dopamine (DA) and serotonin (ST). The voltammetric conditions for electrode preparation in catechin solution were optimized as follows: phosphate buffer at pH 7.4, catechin concentration of 1.0 mM, potential window of 0.2–1.6 V ( vs. Ag/AgCl/KClsat ), scan rate of 50 mV s −1 and cycle number of 15. The prepared electrode showed high electrocatalytic activity for the oxidation of both DA and ST. The highest electrocatalytic activity for DA oxidation was observed in the physiological pH (7.4) buffer solution. Amperometric detection under stirring achieved a current sensitivity of 10.29 nA nM −1 cm −2 to DA in the linear concentration range of 10–780 nM, and 4.81 nA nM −1 cm −2 to ST in the range of 30–2340 nM, with the lowest detection limits of 0.5 and 3 nM for DA and ST, respectively. The resulting biosensor was successfully used to quantify DA and ST in commercial samples with high sensitivity and good stability. In addition, the fact that the oxidized catechin can effectively promote the electron transfer processes of DA and ST may help in understanding the role of catechin in nervous excitement.